2019
DOI: 10.2196/preprints.13776
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Usability, Acceptability, Feasibility, and Effectiveness of a Gamified Mobile Health Intervention (Triumf) for Pediatric Patients: Qualitative Study (Preprint)

Abstract: BACKGROUND Mental disorders are notably prevalent in children with chronic illnesses, whereas a lack of access to psychological support might lead to potential mental health problems or disruptions in treatment. Digitally delivered psychological interventions have shown promising results as a supportive treatment measure for improving health outcomes during chronic illness. OBJECTIVE This study… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…During gameplay, children will put emotions, their coping ability, problem‐solving, activity‐based learning, behaviour change techniques and psychotherapeutic methodologies to practical use. A multi‐site clinical study among paediatric cancer patients showed that using the Triumf game as a digital intervention can improve mental well‐being and boost user engagement (Tark, 2019 ; Tark et al, 2019 ). The game environment enables delivering research‐based content to educate, monitor and support children in a personalized manner, with the underlying objectives of: (a) helping children to better understand their upcoming treatment; (b) offering external support than can promote internal motivation to cope with the treatment; (c) providing children with cognitive challenges and distraction, along with activity‐based learning of healthy behaviours; (d) continuously monitoring the psychological well‐being of children to offer relevant, and personalized, psychoeducation and coping techniques.…”
Section: Methodsmentioning
confidence: 99%
“…During gameplay, children will put emotions, their coping ability, problem‐solving, activity‐based learning, behaviour change techniques and psychotherapeutic methodologies to practical use. A multi‐site clinical study among paediatric cancer patients showed that using the Triumf game as a digital intervention can improve mental well‐being and boost user engagement (Tark, 2019 ; Tark et al, 2019 ). The game environment enables delivering research‐based content to educate, monitor and support children in a personalized manner, with the underlying objectives of: (a) helping children to better understand their upcoming treatment; (b) offering external support than can promote internal motivation to cope with the treatment; (c) providing children with cognitive challenges and distraction, along with activity‐based learning of healthy behaviours; (d) continuously monitoring the psychological well‐being of children to offer relevant, and personalized, psychoeducation and coping techniques.…”
Section: Methodsmentioning
confidence: 99%